Stability of beliefs in mathematics education: a critical analysis - Liljedahl, Peter; Oesterle, Susan; Bernèche, Christian (NOMAD Nordic Studies in Mathematics Education, 2012)
The field of mathematics education has assumed for too long that stability is an inherent and definable characteristic of beliefs. In this article we explore the validity of this claim through the critical analysis of 92 journal articles, conference papers, and book chapters. Using a stringent definition of what it means for a belief to be stable, we conclude that the body of research on mathematical beliefs is inconsistent in its use of this construct. The aggregated results of our analysis also indicate that stability and instability are not mutually exclusive characteristics of beliefs.